KINERJA ORGANISASI UNIT PELAKSANA TEKNIS (UPT) PELATIHAN KERJA USAHA KECIL MENENGAH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI TENGAH - Rahmawati, Rahmawati (Katalogis, 2017)
Based on the problem formulation in this study, the researcher specified that the goal of this study was to provide an overview of the organizational performance of the Technical Implementation Unit for Small and Medium Enterprises Work Training of Central Sulawesi Manpower and Transmigration Department, in terms of productivity, quality of service, responsiveness, responsibility, and accountability indicators. This study used descriptive qualitative method that was supported by data obtained from observations, interviews, and documentations. The informant selection used in this study was purposive sampling. The data analysis technique used was interactive analysis by basing on the process of data reduction, data presentation, verification, and conclusion. The results showed that the organizational performance of the Technical Implementation Unit for Small and Medium Enterprises Work Training of Central Sulawesi Manpower and Transmigration Department in executing work training in terms of productivity, responsiveness, and accountability indicators had been going well, but in the terms of the quality of service and responsibility indicators had not been completely going well. In carrying out its performance, the Technical Implementation Unit for Small and Medium Enterprises Work Training of Central Sulawesi Manpower and Transmigration Department encountered various obstacles, such as lack of training facilities and infrastructures, lack of budgets, and lack of training instructors from the Technical Implementation Unit itself.